Surgical treatment of carcinoma of the oesophagus - Cleland, W. P. (1974)
There is a place for a radical surgical approach to the problem of carcinoma of the oesophagus and it should be our first aim to determine whether such an approach is justified. If radical treatment can not be carried out then the surgeon's only concern is with the preservation of the function of swallowing.